FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI KAKAO RAKYAT DI DESA OGODOPI KECAMATAN KASIMBAR KABUPATEN PARIGI MOUTONG - Halimah Tussadia (Fakultas Pertanian Universitas Tompotika Luwuk, 2023)
The agricultural sector that is favored is the plantation sector that can be carried out by the private sector in the form of large plantations or by the people in the form of community plantations. Plantations are sub-sectors that play an important role in the national economy and have a large contribution to national income, employment provision, export receipts and tax revenues. This study aims to determine the influence of seeds, urea fertilizer, labor on the production of smallholder cocoa farming in Ogodopi Village, Kasimbar District, Parigi Moutong Regency. Determination of respondents using the census method, which is a sampling technique if all members or populations are cocoa farmers as many as 30 people in Ogodopi Village, which will be studied in Ogodopi Village, Kasimbar District, Parigi Moutong Regency as many as 30 respondents, where elements in all populations have the same possibility to be the research sample. The analytical tool used is the analysis of the Cobb-Douglas production function. The results of the analysis showed a significant value of 0.000 for the influence of Seeds (X1), Urea Fertilizer (X2), Labor (X3). simultaneously Fcalculate = 1609.243 > Ftable = 2.57 at α = 5% which means the null hypothesis (H0) is rejected, so that Seeds (X1), Urea Fertilizer (X2), Labor (X3). together (simultaneously) have a real effect on People's Cocoa production in Ogodopi Village, Kasimbar District, Parigi Moutong Regency, Partially, the variables of Seeds and Labor have a real effect on People's Cocoa production in Ogodopi Village, Kasimbar District, Parigi Moutong Regency, while Urea Fertilizer has an intangible effect on People's Cocoa Production in Ogodopi Village, Kasimbar District, Parigi Moutong Regency.